A study of the management and treatment of substance mususe problems in a Regional Health Board in Ireland - Cullen, Kieran (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2009)
This study presents the findings of a research project conducted within a Regional Health Board in Ireland and aimed at evaluating the way in which the public health service responds to alcohol-related problems; the study is also concerned, but in a more limited way, with drug problems.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin.